The Kiai’s Life Stories: A Narrative Inquiry into Fostering Inclusive Character within Pesantren Education - Moh. Irmawan Jauhari; Atika Nailah Syirva; Miftahus Salam; Burhan Djamaluddin; Ainus Sicha; Badrus Badrus; M. Khamim; Zamah tus Saudah Al Farisi (International Journal of Educational Narratives, 2026)
Background. Inclusive character development in pesantren education is increasingly important amid concerns over declining social tolerance and diversity awareness among students. Limited scholarly attention has addressed how informal kiai teachings are systematically integrated into formal educational structures to shape santri values. Purpose. This study analyzes the values embedded in kiai's teachings and examines the patterns through which these values are incorporated into formal pesantren education to strengthen inclusive character formation among santri at Pondok Pesantren Terpadu Al-Kamal Blitar. Method. A qualitative case study approach was employed. Data were collected through in-depth interviews with kiai, teachers, and santri, participatory observations over three months, and analysis of curriculum documents, religious study materials, and institutional regulations. Data were analyzed through reduction, categorization, interpretation, and triangulation to ensure validity. Results. Kiai’s teachings emphasize religious moderation, tolerance, social justice, empathy, exemplary conduct, and concern for others. These values are integrated into formal education through several patterns: curriculum contextualization, open tafsir study sessions, exemplary leadership, inclusive pesantren culture, and value habituation in daily activities, shaping santri who are moderate, socially aware, and open to diversity. Conclusion. The study positions kiai's teachings not merely as informal moral guidance but as a systematic framework for curriculum development, pedagogy, institutional culture, and inclusive character formation